Predictive Value of Circulatingve-catherin in Coronary Artery Disease Patients with Symptomatic Moderate to Severe Chronic Heart Failure (Journal of Medicine, 2015)
Aim: To evaluate the prognostic value of circulating VE-catherinfor cumulative survivalin patients with ischemic chronic heart failure (CHF).Methods: A total of 154 patients withischemic symptomatic moderate-to-severe CHF were enrolled in the study on discharge from the hospital. Observation period was up to 3 years. Blood samples for biomarkers measurements were collected. ELISA method for measurements of circulating level of VE-catherin was used. Concentrations of VEcatherinfor cumulative survival cases due to advanced CHF were tested. Additionally, all-cause mortality, and CHFrelated death were examined.Results: During a median follow-up of 2.18 years, 21 participants died and 106 subjects were hospitalized repetitively. Medians of circulating levels of VE-catherin in survived and died patient cohort were 0.63 ng/ml (95% confidence interval [CI] = 0.55-0.64 ng/ml) and 1.03 ng/ml (95% CI = 0.97-1.07 ng/ml) (P0.755 ng/ml) and low (